Burden of and risk factors for sexual violence among women with and without disabilities in two sub-Saharan African countries - Pierre De Beaudrap; Charles Mouté; Estelle Pasquier; Alice Tchoumkeu; Carole Dongmo Temgoua; Aida Zerbo; Muriel Mac-Seing; Gervais Beninguisse (Taylor & Francis Group, 2022)
Background Available data suggest that women with disabilities have an increased risk of sexual violence, but little is known about the situation of those women living in resource-limited settings. Objectives To assess the burden and examine the drivers of sexual violence among women with disabilities. Methods This is a pooled analysis of two population-based surveys conducted in Cameroon and Burundi. Adults with and without disabilities were randomly recruited from the general population. Structured interviews were conducted at both sites to collect data on participants' functional limitations, life-course history of sexual violence, education, employment, and resources. Only women with disabilities whose impairments started before the age of 10 years (n = 359) and women without disabilities (n = 720) are included in this analysis. The age-adjusted prevalence of violence was computed, and risk factors were assessed using a discrete survival regression and mediation analysis. Results At both sites, the participants with disabilities had a lower education level and had an increased risk of food insecurity. The pooled age-adjusted prevalence of lifetime sexual violence was 19.8% (95%CI:15.3-24.3) among women with disabilities and 11.7% (95%CI:9.3-14.1) among those without disabilities (ORap: 2.0, 95%CI:1.4-2.8). Women with cognitive limitations and those with visual impairments had the highest risk of sexual violence (ORap: 3.5 (95%CI:2.0-6.3) and 2.7 (95%CI:1.4-5.0), respectively). Over the life course, the risk of sexual violence was especially high among women with disabilities who had lived with an intimate partner before the age of 25 years (p < 0.001). Education level mediated approximately one-third of the total association between disability and sexual violence (p = 0.001). There was no evidence of an indirect effect through food insecurity. Conclusion This study provides evidence of the high burden of sexual violence among women with disabilities who live in urban African contexts. The social environment and access to education may be key contributors to this vulnerability.